Drug-induced anaphylaxis in children - Cardinale, Fabio; Amato, Doriana; Mastrototaro, Maria Felicia; Caffarelli, Carlo; Crisafulli, Giuseppe; Franceschini, Fabrizio; Liotti, Lucia; Caimmi, Silvia; Bottau, Paolo; Saretta, Francesca; Mori, Francesca; Bernardini, Roberto (Acta Biomedica Atenei Parmensis, 2019)
Anaphylaxis represents one of the most frequent medical emergencies in childhood. However, as compared to adults, drugs are less common triggers of anaphylaxis in children, with a frequency which is increasing from infancy to adolescence. Deaths seldom occur, maybe because of the paucity of comorbidities in children. Antibiotics and non-steroidal anti-inflammatory drugs (NSAIDs) are the main elicitors in drug-induced anaphylaxis in children. Both immune-mediated (mainly IgE-mediated) and non immune-mediated may be involved. IgG-mediated and complement-mediated mechanisms has been also hypothesized. Correct management relies on a right diagnosis and prompt therapy. A proper work-up is also important to prevent further potentially fatal re-exposures to the same drug or other structurally similar molecules but also unnecessary avoidance of medications not representing the culprit of the episode.